Determinants of Profitability of Listed Real Estate Companies in the Philippines - Aratea, John Lester; Sayson, Gloria Mar (Philippine Management Review; Vol 31 (2024), 2024)
The purpose of this research is to identify the overall internal and external property industry determinants of profitability of listed real estate companies in the Philippines. In particular, this research uses reported annual data from 2013 to 2022. Using a robust random effects (RE) panel regression model with Return on Asset (ROA) as dependent variable, the results show that firm size (-), firm revenue growth (+), liquidity (-), efficiency measured using total asset turnover (+) or measured using cash conversion cycle (-) are significant determinants of profitability. On the other hand, using a robust fixed effects (FE) panel regression model with Return on Equity (ROE) as dependent variable, the results show that while firm revenue growth (+) and efficiency measured using total asset turnover (+) or measured using cash conversion cycle (-) are still significant determinants of profitability, solvency (+) is also another notable factor. The results of this study can help companies in the industry identify firm-specific and macroeconomic factors empirically proven to be important drivers of earning potential so that efforts and resources may be properly channeled to capitalize on them, especially at a recovery period from the effects of the COVID-19 pandemic.